2022
DOI: 10.1136/ijgc-2022-003614
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of PARP inhibitors in elderly patients with advanced ovarian cancer: a systematic review and meta-analysis

Abstract: BackgroundPoly-(ADP-ribose)-polymerase (PARP) inhibitors have shown to be effective as maintenance treatment in patients with advanced ovarian cancer. Although most ovarian cancers develop after age 65, older patients are often under-represented in clinical trials.ObjectiveTo assess the efficacy and safety of PARP inhibitors versus placebo as maintenance therapy in older patients with ovarian cancer.MethodsThis systematic review and meta-analysis was performed in accordance with the Preferred Reporting Items o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…While a previous systematic review of olaparib use on ovarian cancer patients reported that approximately one-third of patients (1435/4364) in eight RCTs were 65 years or older, and hematologic safety was similar to that seen in younger patients. 6 Another subgroup analysis of an RCT found that older patients enrolled in PAOLA-1 achieved similar progression-free survival benefits compared with younger patients, with a similar safety profile. 7 There are several potential reasons for this practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a previous systematic review of olaparib use on ovarian cancer patients reported that approximately one-third of patients (1435/4364) in eight RCTs were 65 years or older, and hematologic safety was similar to that seen in younger patients. 6 Another subgroup analysis of an RCT found that older patients enrolled in PAOLA-1 achieved similar progression-free survival benefits compared with younger patients, with a similar safety profile. 7 There are several potential reasons for this practice.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of olaparib use on ovarian cancer patients reported that approximately one-third of patients (1435/4364) in eight RCTs were 65 years or older, and hematologic safety was similar to that seen in younger patients. 6 Another subgroup analysis of an RCT found that older patients enrolled in PAOLA-1 achieved similar progression-free survival benefits compared with younger patients, with a similar safety profile. 7 Thus, though studies have evaluated the effects of olaparib on the elderly population, these evaluations are limited to subgroup analyses in the setting of an RCT, and there is a dearth of real-world evidence on the use of olaparib in aging populations, especially those using national-level data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research showed that older patients benefit from poly (ADP-ribose) polymerase inhibitor therapy, leading to prolonged progression-free survival similar to younger patients with comparable hematologic safety profiles. 30 …”
Section: Disparity In Clinical Trial Participationmentioning
confidence: 99%
“…Interestingly, a meta-analysis which included results from clinical trials investigating PARPi given as monotherapy or combined with chemotherapy and/or anti-angiogenic drugs compared PARPi with placebo in an elderly cohort aged ≥65 years and in younger patients aged <65 years 57. In this study, safety information was limited to hematologic toxicity and a lower risk of severe anemia was reported in older patients (p=0.04) 57. However, real-world studies should include more geriatric assessment.…”
Section: Which Patient Should Receive Which Parpi: Olaparib Niraparib...mentioning
confidence: 99%